2002
DOI: 10.1038/4151005a
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap modulation of carbon nanotubes by encapsulated metallofullerenes

Abstract: Motivated by the technical and economic difficulties in further miniaturizing silicon-based transistors with the present fabrication technologies, there is a strong effort to develop alternative electronic devices, based, for example, on single molecules. Recently, carbon nanotubes have been successfully used for nanometre-sized devices such as diodes, transistors, and random access memory cells. Such nanotube devices are usually very long compared to silicon-based transistors. Here we report a method for divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
415
1
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 468 publications
(433 citation statements)
references
References 20 publications
13
415
1
4
Order By: Relevance
“…41 Lee et al observed a modified electronic structure of the nanotube in CNT-encapsulated Gd metallofullerenes, as evidenced by low-temperature scanning tunneling microscopy. 42 The above results demonstrate that an electronic interaction exists between metal species and the CNT surfaces and the strength can vary with metals and with the size of CNTs. The modified electronic structure of metal/metal oxide nanoparticles induced by confinement can influence their catalytic activity as redox reactions involve electron transfer between reactants and catalysts.…”
Section: Toward Understanding the Confinement Effects In Catalysismentioning
confidence: 71%
“…41 Lee et al observed a modified electronic structure of the nanotube in CNT-encapsulated Gd metallofullerenes, as evidenced by low-temperature scanning tunneling microscopy. 42 The above results demonstrate that an electronic interaction exists between metal species and the CNT surfaces and the strength can vary with metals and with the size of CNTs. The modified electronic structure of metal/metal oxide nanoparticles induced by confinement can influence their catalytic activity as redox reactions involve electron transfer between reactants and catalysts.…”
Section: Toward Understanding the Confinement Effects In Catalysismentioning
confidence: 71%
“…Nanotubes can be side-gated with selfaligned, regularly spaced metal electrodes tens of nanometers wide [51]. Fullerenes in a SWNT locally alter the electronic states of the SWNT [52,53]. If the electronic states of the nanotube and fullerene are coupled, then this offers a mechanism for qubits to interact over distance through the nanotube.…”
Section: "Peapod" Nanotubesmentioning
confidence: 99%
“…Its spatial resolution, however, is generally limited by wavelength, and information is inevitably averaged over the nanoscale components, despite that they are organized with the greatest care to produce desired functions. In contrast, the real space observation of atomic-scale structures by scanning tunneling microscopy (STM) has lifted the veil from various longstanding problems and is extending the frontiers of science and technology [4][5][6][7][8][9]. However, since the temporal resolution of STM is limited to less than 100 kHz because of the circuit bandwidth, the target carrier dynamics has been beyond its field of vision.…”
mentioning
confidence: 99%